Importance of latency and amplitude values of recurrent laryngeal nerve during thyroidectomy in diabetic patients. (November 2016) - Ozemir, Ibrahim Ali; Ozyalvac, Ferman; Yildiz, Gorkem; Eren, Tunc; Aydin-Ozemir, Zeynep; Alimoglu, Orhan
Abstract: Background: Diabetes mellitus may cause degeneration in the myelin and/or axonal structures of peripheral nerves. The aim of this study was to investigate the effects of diabetic neuropathy on intraoperative neuromonitoring findings such as latency and amplitude values of the recurrent laryngeal nerves during thyroidectomy. To our knowledge this is the first study to report comparison of the electrophysiologic features of diabetic and non-diabetic patients. Materials and methods: One-hundred-and-eleven consecutive patients who received neuromonitoring during thyroidectomy between 2013 and 2015 were included to study. The patients were divided into two groups according to the presence of diabetes mellitus. Pre-thyroidectomy and post thyroidectomy motor response latency and amplitude values of recurrent laryngeal nerves were compared between groups. Neuromonitoring findings, demographic data and postoperative complications were evaluated. Results: The diabetic group consisted of 29 (26.1%) patients while 82 (73.9%) patients were in non-diabetic group. The mean post-thyroidectomy amplitude values (millivolts-mV) of the recurrent laryngeal nerve were significantly lower in diabetic group (0.51 ± 0.26 mV vs. 0, 70 ± 0, 46 mV, p < 0.05), whereas the latency values were significantly higher (2.50 ± 0.86 ms vs. 1.85 ± 0.59 ms, p < 0.01) compared to non-diabetic group. Additionally, post-thyroidectomy latency values were significantly increased compared to the pre-thyroidectomy latency values (2.50 ± 0.86 ms vs. 2.02 ± 0.43 ms) in diabetic group patients (p < 0.05). Although postoperative complication rates were higher in diabetic group (10.3% vs. 5.9%), there were no statistical significance differences. Conclusions: Prolonged latency and decreased amplitude values in recurrent laryngeal nerves of diabetic patients show that diabetic neuropathy of the recurrent laryngeal nerves develop similarly to the peripheral nerves. Increased post-thyroidectomy latency values reveal that the recurrent laryngeal nerve is more susceptible to surgical trauma in diabetic patients. Highlights: Diabetic patients have prolonged post-thyroidectomy latency values than non-diabetic patients. Diabetic patients have decreased post-thyroidectomy amplitude values than non-diabetic patients. Increased post-thyroidectomy latency values detected in diabetic patients compared to pre-thyroidectomy latecies. Recurrent nerve in diabetic patients is more sensitive to the surgical trauma than non-diabetics.